2022
DOI: 10.1038/s41598-022-26551-x
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin biosynthesis genes are required after foliar pathogen infection for the creation of a microbial soil-borne legacy that primes plants for SA-dependent defenses

Abstract: Plants deposit photosynthetically-fixed carbon in the rhizosphere, the thin soil layer directly around the root, thereby creating a hospitable environment for microbes. To manage the inhabitants of this nutrient-rich environment, plant roots exude and dynamically adjust microbe-attracting and -repelling compounds to stimulate specific members of the microbiome. Previously, we demonstrated that foliar infection of Arabidopsis thaliana by the biotrophic downy mildew pathogen Hyaloperonospora arabidopsidis (Hpa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
(71 reference statements)
1
20
0
Order By: Relevance
“…succinic acid), including ursolic acid, were previously linked to soil quality and salt stress mitigation (19,62). Terpenes, flavonoids, coumarins and cinnamic acids were highlighted in both vegetation belts, in agreement with their functions at the plant-microbe interface (8,63). Additional markers, such as lipids, were mainly observed in the rhizosphere of J. frigida .…”
Section: Discussionsupporting
confidence: 75%
“…succinic acid), including ursolic acid, were previously linked to soil quality and salt stress mitigation (19,62). Terpenes, flavonoids, coumarins and cinnamic acids were highlighted in both vegetation belts, in agreement with their functions at the plant-microbe interface (8,63). Additional markers, such as lipids, were mainly observed in the rhizosphere of J. frigida .…”
Section: Discussionsupporting
confidence: 75%
“…The mechanism by which this HAM either directly or indirectly protects against Hpa should be further investigated. However, we previously found that mutant plants impaired in defense signaling that involves the plant hormone salicylic acid, are not protected by a Hpa -induced SBL, suggesting the SBL and associated HAMs work at least partly through activation of salicylic acid-dependent immunity 38 .…”
Section: Discussionmentioning
confidence: 95%
“…The creation of a SBL requires successful infection with the pathogen, as resistant plants that prevent Hpa -infection did not lead to a SBL. Moreover, we previously reported that foliar Hpa infection changes the root exudation profile, and that mutant plants impaired in the biosynthesis of root-secreted coumarins are not able to create a SBL even though they are just as susceptible as the wild type 38 . This indicates that it is the plant that actively assembles its resistobiome in response to attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process ensures a higher availability of iron in the soil and provides increased protection against pathogens. Notably, a recent study demonstrated the importance of the coumarin biosynthesis genes MYB72 and F6′H1 in the development of a microbial soil-borne legacy following foliar pathogen infection (Vismans et al, 2022). This soil-borne legacy, in turn, recruits a microbiome that induces disease resistance and primes salicylic acid-dependent defence mechanisms in plants.…”
Section: Stress Tolerance Genesmentioning
confidence: 99%